Association of Cardiologist Clinic Visits With Cardiovascular Primary Prevention Outcomes Among People With HIV From Underrepresented Racial and Ethnic Groups in the Southern United States - Matthew S. Durstenfeld; C. Larry Hill; Robert M. Clare; Karen Chiswell; Gretchen Sanders; Shamea Gray; Joseph Vicini; Keith Marsolo; Nwora Lance Okeke; Eric G. Meissner; Kevin L. Thomas; Caryn G. Morse; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background People with HIV (PWH) have elevated cardiovascular risk. Underrepresented racial and ethnic groups in the southern United States are disproportionately affected, yet whether cardiology care for this at‐risk group improves blood pressure and lipid control or prevents cardiovascular events is unknown. Methods and Results We evaluated a cohort of PWH from underrepresented racial and ethnic groups who received HIV‐related care at 4 centers in the southern United States during 2015 to 2018 with follow‐up through 2020. Primary outcomes were blood pressure control (<140/90 mm Hg) and lipid control (low‐density lipoprotein cholesterol ≤100 mg/dL) over 2 years and time to first major adverse cardiovascular event. Statistical analyses were adjusted for cohort/site and patient sociodemographic factors, HIV measures, and comorbidities. Among 3972 included PWH (median age, 47 years; 32.6% women) without diagnosed cardiovascular disease, 276 (6.9%) had a cardiology clinic visit. Cardiology visits were not associated with subsequent blood pressure control (adjusted odds ratio, 0.78 [95% CI, 0.49–1.24]; P=0.29) or lipid control (adjusted odds ratio, 2.25 [95% CI, 0.72–7.01]; P=0.16). Over 5‐year follow‐up, patients who had a cardiology visit had a higher risk of a major adverse cardiovascular event, death, and falsification end points, even after adjusting for measured risk factors. Conclusions Among PWH from underrepresented racial and ethnic groups at elevated risk for cardiovascular disease, a cardiology clinic visit was not associated with risk factor improvement or reduced risk of a major adverse cardiovascular event. Our study suggests that seeing a cardiologist is not sufficient to promote cardiovascular health or prevent cardiovascular events among PWH, but with low confidence given the higher risk among those who had a cardiology visit.